The Virome and Its Major Component, Anellovirus, a Convoluted System Molding Human Immune Defenses and Possibly Affecting the Development of Asthma and Respiratory Diseases in Childhood - Freer, Giulia; Maggi, Fabrizio; Pifferi, Massimo; Di Cicco, Maria E.; Peroni, Diego G.; Pistello, Mauro (Frontiers in Microbiology, 2018)
The microbiome, a thriving and complex microbial community colonizing the human body, has a broad impact on human health. Colonization is a continuous process that starts very early in life and occurs thanks to shrewd strategies microbes have evolved to tackle a convoluted array of anatomical, physiological, and functional barriers of the human body. Cumulative evidence shows that viruses are part of the microbiome. This part, called virome, has a dynamic composition that reflects what we eat, how and where we live, what we do, our genetic background, and other unpredictable variables. Thus, the virome plays a chief role in shaping innate and adaptive host immune defences. Imbalance of normal microbial flora is thought to trigger or exacerbate underlying many acute and chronic disorders. A compelling example can be found in the respiratory apparatus, where early-life viral infections are major determinants for the development of allergic diseases, like asthma, and other non-transmissible diseases. In this review, we focus on the virome and, particularly, on Anelloviridae, a recently discovered virus family. Anelloviruses are major components of the virome, present in most, if not all, human beings, where they are acquired early in life and replicate persistently without causing apparent disease. We will discuss how modulation of innate and adaptive immune systems by Anelloviruses can influence the development of respiratory diseases in childhood and provide evidence for the use of Anelloviruses as useful and practical molecular markers to monitor inflammatory processes and immune system competence.